Comparison of Τwo Modules in Sedimentation Process using Mathematical Techniques - Pidurkar, Smita R.; Raut, Seema; Bhorkar, Mangesh (Engineering, Technology & Applied Science Research, 2024)
Raw water must be purified before being distributed to any village, town, or city. To purify raw water, various significant processes must be performed in a water treatment plant, with sedimentation being one of the most important. Solid particles in the form of dirt and other contaminants can be found in raw water, especially during the rainy season, which can be removed through sedimentation. Plate settlers or tube settlers are commonly utilized in sedimentation units to treat water quickly, reducing the detention time to 15-20 minutes. This study modified conventional tubes in terms of manufacturing and repositioning to increase turbidity removal in raw water. The experimental work was carried out for one year to calculate the balanced turbidity of the raw water using conventional and modified square-shaped tube settlers. Mathematical analysis was deployed to compare the output from one year's data from both experimental studies. Regression, R2, relative standard deviation, and ANOVA were employed to analyze the experimental models, and the observed and calculated findings were compared. The results show that the modified tube settlers removed more turbidity from the raw water than the conventional ones.